Juridical Review of the Impact of Pkwt Workers on Trade Unions/Labour Unions in Companies - Tuti Widyaningrum; Turija Turija; Cecep Suhardiman (Fakultas Hukum Dehasen, 2024)
One of the rights of workers / workers in labor relations is the right to freedom of Organization for workers/workers as a forum to express aspirations and freedom of opinion in public and complain. In its implementation to convey aspirations and opinions in public and complain about workers/workers in need of a container. The issue of Trade Unions / Trade Unions is increasingly raised with the impact of the rise of workers / workers of PKWT status on Trade Union Organizations / Trade Unions. It often happens that workers / laborers do not get injustice at work when dealing with the interests of companies or employers. In this study using normative juridical research methods. The main purpose of Trade Union law is to protect the interests and fight for the basic rights of workers. This goal is based on the basic philosophy that workers/laborers are subordinated to employers or companies. Thus the law or legislation in the form as a tool to meneteralisir inequality between workers/laborers with employers or companies. Therefore, when the law cannot balance this subordination, this happens because of a failure in substance and interests that are more in favor of the entrepreneur or company.